Penyelesaian Perkara LGBT Prajurit TNI dalam Sistem Peradilan Militer - Prastiti Siswayani; Nurini Aprilianda; Faizin Sulistyo (Ridwan Institute, 2022)
LGBT (Lesbian, Gay, Bisexual, and Transgender) is a deviant sexual orientation and behavior that is contrary to religious dogma, human nature, and values ​​that live in Indonesian society. It turns out that LGBT behavior has also been committed by TNI soldiers, so that in relation to the resolution of LGBT behavior in the Military Justice system regarding differences in the considerations of the Panel of Judges in the evidence of criminal acts so that in this study it is about the philosophy of the Panel of Judges in proving criminal acts based on Article 103 of the Indonesian Criminal Code. Military Criminal Law and the basis for the implementation of Article 103 of the Criminal Code as well as solutions for setting up LGBT settlements in the future. Apart from that, the research being conducted is normative research with a comparative approach to the decisions of judges in two military courts. prioritizing people of the same sex as a means of channeling their sexual desires is called homosexuality. In conclusion, LGBT behavior in Military Courts is an immoral and immoral behavior that can be subject to strict sanctions in the form of a crime under the provisions of Articles 281 and 103 of the Criminal Code.